Comparative study on proper thermocouple attachment for vapour phase soldering profiling. Issue 1 (1st February 2016) - Géczy, Attila; Kvanduk, Bíborka; Illes, Balazs; Harsányi, Gábor
Abstract : Purpose: – The paper aims to present a comparative study of various thermocouple (TC) attaching methods for the proper measurement of soldering temperature profiling during vapour phase soldering (VPS). The heat transfer process during VPS is different from common methods, while the required heat for reflow is provided by the condensation. The condensate is a flowing layer on the board, where the dynamic behaviour also affects the local conditions on the surfaces. Temperature measurements based on TCs are also affected this way; it is important to investigate the process for deeper understanding. Design/methodology/approach: – Bare printed circuit boards (PCBs) were prepared for standard K-Type TCs attachment with industry standard materials: kapton polyimide tape, aluminium tape, SMD adhesive and high-temperature solder (HTS). Heating experiments were performed in a batch-type VPS oven with Galden LS240 fluid and fixed oven parameters. Findings: – According to the specific attachment requirements, HTS and Alu-tape are the suggested methods for better profiling reliability and repeatability. Alu-tape is the preferred all-around method, for fast, exchangeable, cheap, reliable and repeatable profiling in a VPS oven. It was presented that the heating factor (Q?) gives more reliable comparison overview; the time period-based comparisons may be affected by the thermal inertia, while heating factor also includes temperature conditions at the given time points. Originality/value: – The paper presents the reliability of the presented methods for VPS and present suggestions for the use of different TC ends and attaching materials during condensation heating of the PCBs. Also a new approach on profiling data evaluation based on the heating factor is presented and suggested for wider use.